Establishment and Implementation of the Balingasay Marine Protected Area: A Community-Based Approach - Salmo III, Severino; Turion, Renato; Juinio-Meñez, Marie Antonette; Aliño, Porfirio (Science Diliman: A Journal of Pure and Applied Sciences; Vol 12 No 2 (2000), 2007)
A community-based approach in the establishment and implementation of a marine protected area (MPA) in Balingasay, Bolinao, Pangasinan is presented. The factors necessary to facilitate the successful establishment and implementation of a community-managed MPA include heightening of environmental awareness, community mobilization, and legal/institutional and financial assistance. A heightened environmental awareness encouraged the community to undertake resource management action. The formation of a people’s organization, SAMMABAL (Samahan ng mga Mangingisda at Mamamayan ng Balingasay), was crucial in assessing environmental problems (e.g., overfishing) and identifying the establishment of an MPA as a management tool to address the problem. SAMMABAL was also instrumental in eliciting community support for the issuance of a municipal ordinance in the establishment of the MPA. Subsequently, the organization initiated the patrolling of the MPA. Institutions involved in the community-based management of the MPA also included the multi-sectoral council (BRMC – Balingasay Resource Management Council) and representatives from the barangay council and the municipal government. This institutional arrangement has proven to be very resilient, indicating a high probability of sustaining its successes despite some obstacles and shortcomings. Clear delineation of the role and functions of the institutions and the stakeholders was essential in advancing the initiative. This case study will draw on the lessons from the experience of a four-year community-managed MPA.
Keywords: community-based approach; environmental awareness; management tool; marine protected area (MPA); community mobilization; inter-institutional interaction; CBCRM